Uncertainty, Risk, and Capital Growth - Segal, Gill; Shaliastovich, Ivan (Review of Financial Studies, 2025)
We find that high productivity-based macroeconomic uncertainty is associated with greater accumulation of physical capital despite a reduction in investment and valuations. To reconcile this puzzling evidence, we show that uncertainty predicts lower aggregate depreciation of existing capital, which dominates the investment slowdown. We explain these findings by developing a quantitative production-based model in which firms implement precautionary savings through reducing utilization rather than raising investment. Through this novel intensive-margin mechanism, uncertainty shocks command a quarter of the equity premium in general equilibrium. Flexibility in utilization adjustments also helps explain uncertainty risk exposures in the cross-section of industry returns.